Exploratory Arrangement of City Park Facilities Through Visitor Behavior Mapping (Case Study: Adipura Park in Muara Enim City) - Mita Hargianti; Rika Septiana; Yandra Iskandar; Nasution Iskandar; Win Insani; Husnul Hidayat (Ikatan Peneliti Lingkungan Binaan Indonesia, 2026)
Rapid urban development has increased the public’s need for urban parks as public spaces. However, the lack of a systematic evaluation mechanism based on user behavior has often resulted in facility layouts being out of sync with spatial characteristics and visitors’ activity patterns. This causes park utilization rates to inadequately reflect spatial potential, requiring an empirical approach to understand the relationship between spatial characteristics and user behavior. This study analyzes the distribution of visitor activities and their relationship with spatial characteristics to formulate facility layout recommendations using behavior mapping at Adipura Park in Muara Enim, South Sumatra. A descriptive qualitative approach supported by quantitative data was applied through direct observation over seven days in three time periods. The park was divided into zones based on function and spatial characteristics. Results indicate variations in activity intensity and type across zones. Zones 2 and 3 show the highest utilization levels, while Zone 1 is moderate and mainly circulatory. Zones 4 and 5 tend to be passive due to limited facilities, comfort, and visibility. These findings underscore the importance of aligning facility layouts with user behavior as a basis for urban park planning. The findings provide empirical guidance for designing more responsive, efficient, and user-oriented public park spaces.